2010
DOI: 10.1086/652871
|View full text |Cite
|
Sign up to set email alerts
|

Recognition ofBorrelia burgdorferiby NOD2 Is Central for the Induction of an Inflammatory Reaction

Abstract: Toll-like receptor 2 (TLR2) plays an important role in the recognition of Borrelia bacteria, the causative agent of Lyme disease, but the existence and importance of additional receptors in this process has been hypothesized. In the present study, we confirmed the role played by TLR2 in the recognition of Borrelia bacteria but also demonstrated a crucial role for the intracellular peptidoglycan receptor NOD2 for sensing the spirochete. Cells from individuals who were homozygous for the loss-of-function mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 46 publications
4
52
3
Order By: Relevance
“…burgdorferi triggers the production of inflammatory mediators in macrophages via recognition of both Toll-like receptors (TLRs) and non-TLRs (8,12,22,71,78,95,97). In the present study, gene array analysis identified candidate genes from multiple pathways induced by live spirochetes that were a A corrected one-way analysis of variance was used to analyze the microarray data.…”
Section: Discussionmentioning
confidence: 99%
“…burgdorferi triggers the production of inflammatory mediators in macrophages via recognition of both Toll-like receptors (TLRs) and non-TLRs (8,12,22,71,78,95,97). In the present study, gene array analysis identified candidate genes from multiple pathways induced by live spirochetes that were a A corrected one-way analysis of variance was used to analyze the microarray data.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, proinflammatory cytokine interleukin-1␤ (IL-1␤) is essential for the development of Th17 responses, and B. burgdorferi is a potent inducer of IL-1␤ (25). Recently, it was also demonstrated that caspase-1 is crucial for B. burgdorferiinduced IL-17 responses (26).…”
Section: Interleukin-23 (Il-mentioning
confidence: 99%
“…Several in vitro studies indicate the importance of lipid-modified proteins in the pathogenesis of the infection (6 -8). The immune system recognizes these lipoproteins by different pattern recognition receptors, of which Tolllike receptor 2 (TLR2) 5 and nucleotide-binding oligomerization domain-containing protein 2 (NOD2) are suggested to be the most important (4,9). The activation of pattern recognition receptors after recognition of Borrelia results in the secretion of the proinflammatory cytokine IL-1␤ which is known to be involved in the pathogenesis of Lyme disease (10 -12).…”
mentioning
confidence: 99%